(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The research study explores the literary legacy of Mary Ann Evans, renowned by the pen name George Eliot, a prominent figure in Victorian literature. Eliot’s influential works have made a lasting impact on the realist tradition. The article is dedicated to probing the themes and stylistic nuances embedded in her notable novels, including Middlemarch, Adam Bede, and Silas Marner. Through a thorough analysis, the study aims to unveil the intricacies of Eliot’s literary craftsmanship, shedding light on her substantial role in shaping nineteenth-century realism.